Epidemiological and clinical characteristics of pertussis in children and their close contacts in households: A cross-sectional survey in Zhejiang Province, China - Lin, Luo-Na; Zhou, Jin-Si; Hua, Chun-Zhen; Bai, Guan-Nan; Mi, Yu-Mei; Zhou, Ming-Ming (Frontiers in Pediatrics, 2022)
Background: Despite the expanded immunization programs, the “re-emergence of pertussis” has become a global concern in recent years. At present, the prevalence of pertussis in China is seriously underestimated, and the role of close contact on the disease spreading in children remains unclear. Objectives: Our study aimed to investigate pertussis’s epidemiological and clinical characteristics in children and their close contacts in households, as well as the antimicrobial resistance of Bordetella pertussis (B. pertussis) in Zhejiang Province, China. Methods: We have collected the retrospective and prospective data of children who were suspected of pertussis and their close contacts in households from January 1, 2018, to December 31, 2020, in the Children’s Hospital, Zhejiang University School of Medicine, Hangzhou, Zhejiang, China. Nasopharyngeal swabs were collected and cultured for B. pertussis. Antibiotics susceptibility test was determined by using E-test methods. Clinical information was collected from the medical records systems. Results: A total of 350 index patients and their 946 family members (close contacts in households) from 350 families were recruited. B. pertussis strains were isolated from 130 (37.1%) index patients and 116 (12.3%) close contacts. 37 index patients had negative culture results for B. pertussis while their close contacts were positive. A higher positive rate was found in female adults than that in male adults (16.3% vs. 5.1%, P<0.01). The positive rate in index patients from multi-child families was significantly higher than that from one-child families (51.7% vs. 37.7%, P<0.05). 53.3% of the pertussis patients were under 6 months of age. 98 (75.4%) isolates had MICs ≥256 mg/L to erythromycin, azithromycin, and clindamycin, and 127 (97.7%) had MICs<0.016 mg/L to piperacillin. Conclusions: Infants under 6 months of age are at high risk of pertussis, and close contacts in households are prone to cluster infection. Culture for B. pertussis both in children and their close contacts contributes to improving the diagnosis rate of pertussis in children. Isolates of B. pertussis in China are highly resistant to macrolides.